Education for employability: focus of educational research - Díaz Gómez, Eduardo Raúl (IE Revista de Investigación Educativa de la REDIECH, 2019)
There is interest within academic circles in discussing the role of universities in preparing students for employment and the development of employability competencies. This interest developed from the high unemployment rates of recent college graduates in some countries. The purpose of the article was to support this discussion and frame it in terms of the achievements of scholars involved in this type of research. Under a qualitative content analysis approach, 46 articles on employability were examined. The analysis emerged six major themes about the work that universities engage in to promote employability. These categories are: cross-discipline competencies, equity, employability promotion, internationalization, educational programs, and labor market. These categories represent teaching, service, and research opportunities for teachers and academics. Implications are discussed in terms of the contributions attributed to Boyer and others who argued in favor of articulating the functions of the professoriate.